Sustainable Cultural Tourism and Community Development: The Perspectives of Residents' and the Application of Social Exchange Theory - Yoopetch, Chanin (Journal of Urban Culture Research, 2022)
This study aims to examine the significant factors affecting residents 'support for tourism during one of Thailand's most celebrated festivals - the candle festival, and develop practical guidelines to support its sustainability. Data was collected from residents of the local community where the candle festival is held. Guided by the Social Exchange Theory, the measurements used in this current study were adapted from the past literature concerning the theory. In this research, the dependent variable was residents' support for sustainable festival tourism, and the independent variables included community pride, sense of community, perceived cost, perceived benefit and attitudes towards tourism development. The findings showed that attitude towards tourism development, sense of community, community pride, and perceived benefits significantly affected the residents' support for sustainable festival tourism.